DAYA HAMBAT EKSTRAK DAUN MENGKUDU (Morinda citrifolia L.) TERHADAP PERTUMBUHAN BAKTERI PENYEBAB DIARE - Widiana, Rina; Indriati, Gustina; Harsinta, Nora (IAIN Batusangkar, 2011)
Diarrhea is the second biggest cause of infant death in Indonesia. Diarrhea can caused by several factors, one of them is bacteria. The most common bacteria which cause diarrhea are Escherichia coli and Salmonella sp. The common treatment for the diarrhea victim uses synthetic antibiotic. Unfortunately, it gives side effect such as; fever, allergic, headache and resistance to strain microbe. Therefore the alternative treatment which does not cause side effect to the diarrhea victim is using antibiotic from plant need to be found immediately. One of them is using the extract from leave of morinda (Morinda citrifolia L.). Thus this research had been conducted in order to find out morinda leave extract in restricting the growth of E. coli and Salmonella sp. This research was conducted on Desember 2010 in Biology Laboratory of Biology department of STKIP PGRI West Sumatera. Experiment design is randomized completely design with six treatment and four replication. Treatment A used Amoxicilin and treatment B used morinda leave extract with level of concentration15 %, C 20 %, D 25 %, E 30 % and F 35 %. The method paper diffusion used to determine the diameter of inhibition area of morinda leave extract. The data was analyzed with ANOVA and continued with least significant different test with p<0.05. The result showed that mengkudu leave extract can decrease the growth of E. coli and Salmonella sp bacteria where Salmonella sp is more sensitive than E. coli.Key words: diarrhea, escherichia coli, salmonella sp, morinda leave extract, amoxicilin